1999
DOI: 10.1212/wnl.52.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Progressive motor deficits in lacunar infarction

Abstract: The progression of motor deficits is associated with a relatively poor functional outcome. Diabetes mellitus and the severity of motor deficit on admission may predict progression of motor deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
113
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 25 publications
13
113
3
Order By: Relevance
“…The frequency and significance of perfusion abnormality in LI was previously addressed in several small series. [26][27][28] One of the largest studies (22 patients) demonstrated MTT abnormality in 68.2% of LIs, comparing favorably with 61% in the present series.…”
Section: Discussionsupporting
confidence: 65%
“…The frequency and significance of perfusion abnormality in LI was previously addressed in several small series. [26][27][28] One of the largest studies (22 patients) demonstrated MTT abnormality in 68.2% of LIs, comparing favorably with 61% in the present series.…”
Section: Discussionsupporting
confidence: 65%
“…There has been no clear explanation on the mechanism of progressing lacunar infarction and motor recovery after induced hypertension [5,[22][23][24][25]. Nevertheless, there is a case report of the benefit of induced-hypertension, which early neurological deterioration due to perfusion defect in a progressing large artery territory infarction was restored [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lacunar infarction have a better prognosis than those with other stroke subtypes, 20) although neurological deterioration was observed in 20-40% of patients with acute lacunar infarction. 18,22,24,25) Effective therapy for patients with lacunar infarction is very desirable, because they are likely to return to normal lives. Edaravone is a promising radical scavenger for the treatment of such patients with acute lacunar stroke.…”
Section: Discussionmentioning
confidence: 99%